Cultural worldviews and perceived risk of colon cancer and diabetes. (17th August 2020) - Chen, Xuewei; Orom, Heather; Kiviniemi, Marc T.; Waters, Erika A.; Schofield, Elizabeth; Li, Yuelin; Hay, Jennifer L.
ABSTRACT: Individuals with different cultural worldviews conceptualise risks in distinct ways, yet this work has not extended to personal illness risk perception. The purpose of this study was to 1) examine the relationships between two types of cultural worldviews (Hierarchy-Egalitarian; Individualism-Communitarianism) and perceived risk (perceived severity and susceptibility) for diabetes and colon cancer, 2) test whether health literacy modifies the above relationships, and 3) investigate whether trust in government health information functions as a putative mediator of the relations between cultural worldviews and disease perceived risk. We recruited (N = 600) participants from a nationally-representative Internet survey panel. Results were weighted so the findings are representative of the general United States population. People with a more hierarchical worldview expressed lower perceived susceptibility to developing both diabetes and colon cancer, and perceived these diseases to be less severe, relative to those with a less hierarchical (more egalitarian) worldview. There was no significant association between individualistic worldview and perceived risk. Health literacy modified the relationships between hierarchical worldview and perceived risk; the associations between hierarchical worldview and lower perceived severity were stronger for those with limited health literacy. We did not observe indirect effects of cultural worldviews on perceived risk through trust in health information from government sources. It may be useful to identify specifically tailored risk communication strategies for people with hierarchical and individualistic worldviews, especially those with limited health literacy, that emphasise their important cultural values. Further research examining cultural components of illness risk perceptions may enhance our understanding of risk-protective behaviours.